PENGARUH LATIHAN TENDANGAN LURUS KE SANSAK TERHADAP POWER OTOT TUNGKAI PADA ATLET JUNIOR PENCAK SILAT PUTRA PAT BAN BU PEKANBARU - Romadiana Romadiana; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: the problem in this research is about the athlete is still less than maximum in straight kick. It proves when they are practicing and competing lack of power and the strength of leg muscle that the athlete has so the athlete isn’t maximum to do the straight kick. The straight kick is can be avoided and read by the enemy. It due to lack of speed in doing straight kick.the purpose of this research is to know about the effect of straight kick training to samsak on leg of power muscle on junior athlete at martial arts putra pat ban bu Pekanbaru.the kind of research that is used is experiment and use research design one grup preetest-posttes design. The population in this research at martial arts pat ban bu club Pekanbaru are 5 People. As for example of technique is uesd is total sampling (sampel jenuh ). Where all of the population is become the example.therefore the example of this research is 5 people example at martial arts pat ban bu Pekanbaru. The instrument that is done in this research is long jump test without prefix. After that the data is proccesed by statistics. To test the normality by lilifors test at the level of significance a (0.05). The hypothesis proposed is the effect of straight kick exercises to samsak on leg of power muscle on junior athlete at martial arts putra pat ban bu Pekanbaru. Based on analisis test produce Tcount3,60 and Ttable2.132 it mean Tcount> Ttable. Based on the analisys of statistic data. There is an average pre test of 215.8 and a post test average of 247.8 so the data is normal to the effect of straight kick traning to samsak on leg of power muscle on athlete at martial arts putra pat ban bu PekanbaruKey Word: The Straight Kick Training, The Leg Of Power Muscle